Mackerel Trypsin Purified from Defatted Viscera by Supercritical Carbon Dioxide - Byung-Soo Chun; Hideki Kishimura; Sitthipong Nalinanon; Sappasith Klomklao; Soottawat Benjakul (My University, 2011)
Viscera of mackerel ( Scomber sp.) were defatted by supercritical carbon dioxide (SCO 2 ) treatment. Trypsin (SC-T) was then extracted from the defatted powder and purified by a series of chromatographies including Sephacryl S-200 and Sephadex G-50. The purified SC-T was nearly homogeneous on SDS-PAGE, and its molecular weight was estimated as approximately 24,000 Da. N -terminal twenty amino acids sequence of SC-T was IVGGYECTAHSQPHQVSLNS. The specific trypsin inhibitors, soybean trypsin inhibitor and TLCK, strongly inhibited the activities of SC-T. The pH and temperature optimums of SC-T were at around pH 8.0 and , respectively, using N α - p -tosyl-L-arginine methyl ester as a substrate. The SC-T was unstable below pH 5.0 and above , and it was stabilized by calcium ion. These enzymatic characteristics of SC-T were the same as those of other fish trypsins, especially spotted mackerel ( S. borealis ) trypsin, purified from viscera defatted by acetone. Therefore, we concluded that the SCO 2 defatting process is useful as a substitute for organic solvent defatting process.
Keywords: Defatting; Sephadex; Meat and Animal Product Quality